Perancangan Mesin Pencacah Polimer Komposit untuk Aplikasi Komponen Fuel Cell - Maulana, M Rizky; Fauji S, Ahmad; Iswandi, Iswandi; Umroh, Bobby (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study aims to design a composite polymer shredding machine with a capacity of 50 kg/h to enhance recycling efficiency. The machine is powered by a 3 HP electric motor, equipped with a 1:50 ratio reducer and 200 mm diameter blades. Technical analysis encompasses calculations of cutting force, torque, and throughput, supported by CAD/CAE modeling to validate the structural design. The results show a shredding capacity of 833.33 g/min, cutting force of 47.088 N, and torque of 9.4176 Nm. The machine features a compact, energy-efficient design and delivers consistent output. A UNP steel frame ensures structural stability against dynamic loads. With good efficiency and sustainability, this design is suitable for small to medium-scale industries involved in composite polymer material processing.